The practice of weight loss in combat sports athletes: A systematic review - Zhong, Y.; Song, Y.; Artioli, G. G.; Gee, T. I.; French, D. N.; Zheng, H.; Lyu, M.; Li, Y. (Nutrients, 2024)
The aim of this systematic review is to comprehensively assess the weight loss (WL) practices in different combat sports (CS). The review protocol was preregistered with PROSPERO [CRD42023487196]. Three databases were searched (Web of Science, EBSCOhost, and PubMed) until 8 December 2023. Eligible studies had to meet five criteria: they must have been (a) written in English, (b) published in a peer-reviewed journal, (c) used a survey design to investigate the WL practices of CS athletes, and (d) reported the WL methods used by athletes using a five-point scale. Twenty-six studies (3994 participants from 14 CS) were included. This review found that (1) WL is highly prevalent in CS athletes; (2) many CS athletes started losing weight for competition as teenagers two to three times a year; (3) CS athletes usually lose <5% body weight in 7-14 days before competition; (4) increasing exercise and gradually dieting are the most commonly used WL methods; and (5) the influence of scientific practitioners on athletes is negligible. The habitual practices of CS athletes may be relatively harmless, but in some special cases, CS athletes also perform extreme WL practices. Scientific practitioners have little influence on their WL practices, which may form a vicious cycle of non-qualified influence.